PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KUALITAS KEPUTUSAN MELALUI KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN DENGAN SALING KETERGANTUNGAN SEBAGAI VARIABEL MODERATING (BBM (Buletin Bisnis & Manajemen), 2015)
AbstractManagement Accounting System (MAS) is a procedure and systems formal that use information to maintain and provide an alternative of the various activities the company. Characteristics of accounting information management useful based on managerial perceptions as decision makers are categorized into four properties, namely the scope, timeliness, aggregation, integration. This research aims to test the effect of the use of information technology to the quality of decisions through the characteristics of management accounting system (SAM) with interdependence as a moderating variable. This research use survey method with sampel is Small and Medium Enterprises (SMEs) in Kabupaten Rembang, with cluster sampling obtained sample 138 SMEs. Data were collected by means of questionnaires directly deliver to the address of the respondents, as well as its own returns the address of the respondents picked according to predetermined promise. Analysis of the data using linear regression. This research suggest that information technology influence positive to SAM and SAM influence positive to decision quality. This is suggest that SAM indirectly can mediate the relationship between information technology with decision quality. Morever, this research also refer that the SAM influence on the quality of decisions is stronger when moderated by interdependence. Keyword: information technology, quality of decisions, characteristics of management accounting system, interdependence